ANALISIS LITERASI DAN DISPOSISI MATEMATIS SISWA PADA MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT DENGAN PENDEKATAN RME BERBANTUAN SCHOOLOGY - Kiki Komalia; St. Budi Waluya; Tri Sri Noor Asih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Mathematics learning achievement has not shown satisfactory results and students' mathematical literacy abilities are still not optimal. It is necessary to strive for learning innovation in schools with indicators of mathematical literacy and attention to students' mathematical dispositions. This research aims to determine the quality of mathematics learning using the Missouri Mathematics Project learning model with the RME approach assisted by Schoology and students' Mathematical Literacy in terms of Mathematical Disposition. This research uses a mixed methods method with a sequential explanatory design, namely collecting quantitative data then collecting qualitative data and analyzing both data. The population of this study were all seventh grade students at SMP IT Insan Scholar Semarang. Sampling in this study used random sampling techniques. The results of this research show that (1) the Missouri Mathematics Project learning with the RME approach assisted by schoolology has quality on students' mathematical literacy. (2) Students with a high mathematical disposition master the components of communication, mathematization, reasoning and argument, and Using mathematics tools very well, the components of representation, devising strategies for solving problems, and using symbolic, formal, and technical language and operations are well mastered. Students with a mathematical disposition are mastering communication, mathematization, devising strategies for solving problems and using symbolic, formal, and technical language and operations well, the components of representation, reasoning and argument and using mathematics tools quite well. Students with a low mathematical disposition can master the communication and representation components, not well, and the other five components quite well.